Two‐day low‐dose dexamethasone suppression test more accurate than overnight 1‐mg in women taking oral contraceptives. Issue 3 (26th May 2021) - Carton, Tiphaine; Mathieu, Elise; Wolff, Fleur; Bouziotis, Jason; Corvilain, Bernard; Driessens, Natacha
Abstract: Introduction: Late‐night salivary cortisol (LSaC) and 24‐h urinary free cortisol measurement, and overnight 1‐mg dexamethasone suppression test (1 mg‐DST) are the first‐line screening tests recommended for Cushing's syndrome. Through elevations in the level of cortisol‐binding globulin, oral contraceptive agents lead to increases in the total plasma cortisol concentration, yielding false‐positive 1 mg‐DST results. Objective: To compare the accuracy of the overnight 1‐mg DST and two‐day low‐dose DST (2d‐DST) in female volunteers taking combined oestrogen‐progestin oral contraceptives (COCs). Methods: This prospective study enrolled 30 healthy participants. Their plasma cortisol response levels were compared after the 1‐mg DST and 2d‐DST and classified into three categories: normal (≤50 nmol/L), doubtful (51–138 nmol/L) and abnormal (>138 nmol/L). Salivary cortisol was also measured at late night and after the DSTs. Results: Following the 1‐mg DST and 2d‐DST, the plasma cortisol concentrations decreased to a median of 69 nmol/L and 37 nmol/L, respectively ( p  < 0.001). A statistically significant higher proportion of unclear or abnormal results were observed after the 1‐mg DST (63%) than after the 2d‐DST (27%) ( p  = 0.004). None of the values were >138 nmol/L after the 2d‐DST, while 11% of them were abnormal after the 1‐mg DST ( p  = 0.25). No LSaC value was abnormal. Conclusion: Our results suggest that, when late‐night salivary cortisol is not available, the 2d‐DST could be a better screening option than the 1‐mg DST for women taking oral contraceptive agents who are reluctant to stop them. This finding requires confirmation in those with a suspicion of hypercortisolism. Abstract : This study compared the accuracy of the overnight 1‐mg dexamethasone suppression test (1 mg‐DST) and two‐day low‐dose DST (2d‐DST) in female volunteers taking combined oestrogen‐progestin oral contraceptives (COCs). Our results confirm that in women taking oral contraceptives, 1‐mg DST is not accurate as first‐line screening test. Our results suggest that, when late‐night salivary cortisol is not available, the 2d‐DST could be a better screening option than the 1 mg‐DST for women using oral contraceptive agents who are reluctant to stop them. The cessation of oral contraception may not always be mandatory for the performance of the 2d‐DST, particularly if the initial cortisol concentration is lower than 900 nmol/L.